2020
DOI: 10.1108/bij-10-2019-0467
|View full text |Cite
|
Sign up to set email alerts
|

Performance appraisal and premature sign-offs and underreporting of chargeable time of external auditors – internal benchmarking of experience and gender

Abstract: PurposeThe research paper investigates auditors' dysfunctional behaviors in relation to performance appraisals. It explores the dysfunctional audit behavior (DAB) differences among experienced/inexperienced and male/female auditors when expecting performance appraisals, how their perception of DAB changes and how their reactive-outcomes vary.Design/methodology/approachThe survey comprises statements pulled from performance appraisal templates used by the Big Four audit firms in the UK. The sample has been test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 51 publications
1
16
0
2
Order By: Relevance
“…Comparing performance to quantitative standards, on the other hand, allows for assessments of institutional shifts in norm vs innovation. Nehme, Michael, and Kozah [15] argue that universities should focus less on internal and more on external benchmarking because of the challenges they provide to the learning process; about where improvement might occur and to the commitment to implementation over the long term. These include: a) A concentration of the results rather than processes; b) A concentration of the best vs good practices, whereby good practice is considered and best practices are defined by a high level of practice considered in the benchmark; c) A test of progressive improvement; d) An identification of a benchmark in order to measure the effectiveness of a functionality in stead of countable.…”
Section: Benchmarkingmentioning
confidence: 99%
“…Comparing performance to quantitative standards, on the other hand, allows for assessments of institutional shifts in norm vs innovation. Nehme, Michael, and Kozah [15] argue that universities should focus less on internal and more on external benchmarking because of the challenges they provide to the learning process; about where improvement might occur and to the commitment to implementation over the long term. These include: a) A concentration of the results rather than processes; b) A concentration of the best vs good practices, whereby good practice is considered and best practices are defined by a high level of practice considered in the benchmark; c) A test of progressive improvement; d) An identification of a benchmark in order to measure the effectiveness of a functionality in stead of countable.…”
Section: Benchmarkingmentioning
confidence: 99%
“…However, most studies found that the main reasons leading to PMSO are time constraints, mainly time budgets and time deadlines (Rhodes, 1978;Pierce and Sweeney, 2004;Soobaroyen and Chengabroyan, 2006;Paino et al, 2010;Khan et al, 2015;Nehme et al, 2016). Some other studies have also proposed a change in DAB and PMSO when auditors are expecting a performance appraisal (Nehme, 2017;Nehme et al, 2019Nehme et al, , 2021.…”
Section: Medar 312mentioning
confidence: 99%
“…A scarcity of studies have examined multiple countries, notably a study by Nehme et al (2019) that examined this association in other cultural contexts, but failed to take into consideration the impact of gender on DAB. On the other hand, Nehme et al (2021) have recently observed the impact of gender differences of auditors on their perception of DAB, but the study was conducted in a single western cultural context. Unlike previous studies on the topic that have mostly surveyed experienced auditors in Big Four audit firms (Nehme et al, 2019(Nehme et al, , 2021, this paper knowingly addresses senior accounting students having some degree of audit experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research examining factors originating from individual auditors as mediators that encourage under-reporting time is still limited. Prior studies focused on professional commitment (Herda & Kasey, 2016), premature sign-offs (Rabih Nehme, Michael, & Kozah, 2020), and personability traits (Aamir, Rasid, Baskaran, & Manzoor, 2018). This research included individual psychological aspects.…”
Section: 1mentioning
confidence: 99%